Enzyme-active liquid coacervate microdroplets as artificial membraneless organelles for intracellular ROS scavenging. (6th July 2022) - Chen, Yufeng; Yuan, Min; Zhang, Yanwen; Zhou, Shaohong; Wang, Kemin; Wu, Zhenjun; Liu, Jianbo
Abstract : Catalase-containing coacervate microdroplets, developed as artificial membraneless organelles with unique liquid compartments, were integrated into living cells to scavenge intracellular massive reactive oxygen species and recover cell viability. Abstract : Artificial organelles are microcompartments capable of performing catalytic reactions in living cells to replace absent or lost cellular functions. Coacervate microdroplets, formed via liquid–liquid phase separation, have been developed as membraneless organelles that mimic the dynamical organization of liquid organelles. However, the further studies focusing on cellular implanting of coacervate microdroplets in living cells to supplement the dysfunction of natural cells are still rare. Here catalase (CAT)-containing coacervate microdroplets, developed as artificial membraneless organelles with unique liquid compartments, were integrated into living cells to scavenge intracellular massive reactive oxygen species (ROS) and recover cell viability. The enzyme-containing coacervate microdroplets were constructed by sequestering CAT in poly(dimethyldiallylammonium chloride) (PDDA)/polyacrylic acid (PAA) coacervate microdroplets; their liquid-like fluidity was revealed by fluorescence recovery after bleaching, and coalescence experiment in vitro and in living cells. After cellular internalization, the coacervate microdroplets remained in the polymer-rich dense phase and retained enzymatic activities. CAT-mediated H2 O2 removal and ROS scavenging in living cells decreased the cytotoxicity of H2 O2, improving cell viability. The cell internalization of coacervate microdroplets in vitro provides a novel approach for designing artificial membraneless organelles in living cells. The strategy of using artificial organelle-mediated enzymatic reactions to supplement cellular dysfunctions can be exploited for their further biomedical applications.